Hupermine A, a novel C16N2-type Lycopodium alkaloid from Huperzia phlegmaria - Hirasawa, Y.; Kato, Y.; Wong, C.P.; Uchiyama, N.; Goda, Y.; Hadi, A.H.A.; Ali, Hapipah Mohd; Morita, H. (Elsevier, 2014)
A novel C16N2-type Lycopodium alkaloid consisting of a quinolizidine with a 6-dimethylaminohexyl side chain, hupermine A (1), was isolated from the club moss of Huperzia phlegmaria, and the structure and relative stereochemistry were elucidated on the basis of spectroscopic data.